The Influence of Local Economic Policy on the Growth of MSME Furniture in Sampang Regency From A Business Eligibility Point of View - M. Syarifudin Hidayatullah (Penerbit Hellow Pustaka, 2024)
This study analyzes the influence of local economic policies on the growth of furniture MSMEs in Sampang Regency. As an important sector in the local economy, furniture MSMEs contribute to employment and community income. Through a qualitative descriptive method, data was collected from interviews, observations, and literature studies. The results show that local economic policies have significant positive impacts, such as increased access to financing, production capacity, and market expansion. However, challenges such as bureaucracy and dependence on subsidies were also found. Enabling factors such as infrastructure, raw materials, and financial support play an important role. The case studies point to innovation and technology as keys to success. This research recommends improved policies and collaboration between the government, private sector, and community to support the growth of furniture MSMEs.